Plan estratégico de marketing para la Empresa Carlos Armando Carchi de la ciudad de Loja, Provincia de Loja - Izquierdo Celi, Carlos Alberto (2018)
The general objective of this thesis is to establish marketing strategies for the company Carlos Armando Carchi of the city of Loja. This study considered the conceptual elements corresponding in importance and that constitute the bibliographic basis for the development of this research work. To this end, the specific objectives set out in the thesis project were developed, among which, first, a Situational Diagnosis of the company was made, which allowed to consider relevant aspects of the company that exist at the present time. The methodology and the techniques used to carry out this research, bibliographical consultations, review of documents, direct observations of the operation and services provided by the company were applied; In addition, an interview was conducted with the Manager; surveys were applied to 318 permanent clients of the company and a total of 20 surveys to the employees that work in the company in order to know the positioning of the company in the market and that through it the information was collected in order to have a clearer and more reliable vision of the solutions that were required to pose. Then proceeded to make the determination of the same opportunities that are: new technologies, Complications to manage a company of this due to a large investment, The company offers very high quality product and the competition has products similar to ours but of lower quality. The 6 weaknesses are: economic instability, growth of competition, prepare your resources efficiently because competition is growing, high tax rates, instability by government measures and customers have several options to choose from in the market. After determining the factors, the matrix of external factors was elaborated giving us as a result 2.49 The data collaborated to formulate the strengths: Manager knows how to run the company, high degree of leadership, image and prestige of the organization, excellent quality products, excellent distribution of the product, quality of customer service, good use factor of the plant, technology appropriate for the company. Weaknesses: Low prices compared to the competition, does not have promotions in sales, financing with high taxes, lack of information systems and low internal and external communication. With these data it was possible to determine the matrix of internal factors that gave us a total of 2.58 With these considerations through the High Impact SWOT Matrix, four objectives were proposed, among which we have to attract new clients and build loyalty to the company, aiming to increase daily service and therefore improve profitability and will have a cost of $ 2,800. Carry out an advertising plan to publicize the services and products offered by the company, all this will cost $ 1, 507.20 Create an incentive plan for the company's personnel, this will cost $ 2,000, and Implement a plan of promotions for the increase of the sales with a cost of $ 3,200, these objectives give as costs a value of $ 9, 507,20 dollars. 7 Based on the interviews and surveys, the managers, workers and customers of the company, it is determined that it does not have a Marketing Plan, which allows improving the product to customers and providing a better service. Finally, the conclusions and recommendations needed for the success of the proposal are put into consideration.